Analysis of Mistuned Dynamic Response of Tuned Flexible Mechanism - Yu Linchong (Jixie chuandong)
The tuned mechanism has mistuned dynamic response when significant flexibleness of components and high speed of mechanism are considered.In order to research mistuned responses,a virtual prototype model of tuned flexible mechanism is applied to simulate kinematics and dynamics.Dynamic responses are simulated in case of mistuned force and mistuned mass.The random parameter sampling data are computed by Monte Carlo method and stochastic response distribution is given by statistical analysis.The results showed that there are mistuned responses in periodical flexible mechanism.The mistuned responses are propagated in form of components vibration in flexible mechanism.The research has laid foundation on vibration localization features of mistuned mechanism.